Palliative care and Parkinson's disease: Meeting summary and recommendations for clinical research. (April 2017) - Kluger, Benzi M.; Fox, Siobhán; Timmons, Suzanne; Katz, Maya; Galifianakis, Nicholas B.; Subramanian, Indu; Carter, Julie H.; Johnson, Miriam J.; Richfield, Edward W.; Bekelman, David; Kutner, Jean S.; Miyasaki, Janis
Abstract: Introduction: Palliative care is an approach to caring for patients and families affected by serious illnesses that focuses on the relief of suffering through the management of medical symptoms, psychosocial issues, advance care planning and spiritual wellbeing. Over the past decade there has been an emerging clinical and research interest in the application of palliative care approaches to Parkinson's disease (PD) and outpatient palliative care services are now offered by several movement disorders centers. Methods: An International Working Group Meeting on PD and Palliative Care supported by the Parkinson's Disease Foundation was held in October 2015 to review the current state of the evidence and to make recommendations for clinical research and practice. Results: Topics included: 1) Defining palliative care for PD; 2) Lessons from palliative care for heart failure and other chronic illnesses; 3) Patient and caregiver Needs; 4) Needs assessment tools; 5) Intervention strategies; 6) Predicting prognosis and hospice referrals; 7) Choice of appropriate outcome measures; 8) Implementation, dissemination and education research; and 9) Need for research collaborations. We provide an overview of these discussions, summarize current evidence and practices, highlight gaps in our knowledge and make recommendations for future research. Conclusions: Palliative Care for PD is a rapidly growing area which holds great promise for improving outcomes for PD patients and their caregivers. While clinical research in this area can build from lessons learned in other diseases, there is a need for observational, methodological and interventional research to address the unique needs of PD patients and caregivers. Highlights: Summary of first Parkinson's disease (PD) & Palliative care international meeting. PD patients and caregivers have palliative care needs from time of diagnosis. Lessons from cancer and heart failure can help guide palliative care efforts in PD. Preliminary data suggests outpatient palliative care may be effective in PD. Research is needed on outcome measures, need assessment and hospice guidelines.